Nonfatal Agricultural Injuries in Florida: Crop Production - Joelle Francois; Cassandra Ward; Serap Gorucu (EDIS)
This publication examines nonfatal injuries and illnesses among crop production workers in Florida. Written by Joelle Francois, Cassandra Ward, and Serap Gorucu, and published by the UF/IFAS Department of Agricultural and Biological Engineering, October 2022.